Identification and Analysis of Diversity of Soil Microorganism Colonies in Limestone Reclamation Land - Nurtjahyani, Supiana Dian; Oktafitria, Dwi; ., Sriwulan; Zaenal Arifin, Ahmad; Purnomo, Eko (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 2 (2020): ATBES, 2020)
Reclamation of land used for mining is very important because it is related to microbial activity in the soil which has an impact on soil fertility. The purpose of this study is to identify and analyze the diversity of bacterial colonies in the reclaimed land of the former Limestone Mining. The method used in this research was a laboratory experimental method. The results of the study showed that 6 bacterial isolates were found and the highest total plate count in GPS land (GPS system) is 1.97 X 10 6 cfu, the dominant colony characteristics were irregular shapes, flat edges and milky white color.